An Extremely Rare Case Report On Patent Vitello Intestinal Duct Leading to Double Proximal and Distal Ileal Intussusception - Daniel, Tigabu; Mekonen, Yidnekachew (Journal of Medical Health Research and Psychiatry, 2024)
Background: A very uncommon condition known as double intussusception results from both proximal and distal ileal segment protrusion into the patent vitelline duct. At 5 to 9 weeks gestation, the vitelline duct that will cause an intussusception is often obliterated. Case report: A 22-day-old male neonate was delivered to a Para II mother after 9 months of amenorrhea via spontaneous vaginal delivery at the health clinic. He had an unknown weight and screamed shortly after birth. Double intussusception via patent vitelline duct was identified; the intussusception was manually reduced; segmental ileal resection, including the duct, was performed; end-to-end ileal anastomosis was performed; and umbilical repair by purse string was completed. The patient was admitted to the ward for 7 days, and then discharged after improving. He is now in his sixth month of post-operative recovery and is not complying. Conclusion: Although it is highly unusual for a surgeon to witness late-onset double intussusception via a patent vitelline duct, it is critical to be aware of its incidence and treatment.